Determining the safety of enoxaparin prophylaxis in critically ill patients with severe renal insufficiency – The PACER pilot study. Issue 144 (August 2016) - Castellucci, Lana A.; Shaw, Joseph; Giulivi, Antonio; Edwards, Cedrick; Carrier, Marc; Patel, Rakesh
Highlights: Critically ill patients with severe renal insufficiency are at risk for venous thromboembolism. These patients are at risk for anticoagulation bioaccumulation. We achieved the minimum monthly recruitment target; a larger study is likely feasible. Bioaccumulation of enoxaparin was not demonstrated.